Can Oxidative Stress Parameters Be Used as Biomarkers for the Discrimination of Malignant Head and Neck Tumors - DOĞAN, REMZI; Dogan, REMZİ; TUĞRUL, SELAHATTİN; HAFIZ, Aysenur Meric; ÖZTURAN, ORHAN; TUGRUL, Selahattin; KOÇYİĞİT, ABDÜRRAHİM; Ozturan, ORHAN; KESKIN, Siddika; Kocyigit, ABDÜRRAHİM (My University, 2016)
Objective: In this study the authors have investigated oxidative stress parameters in sera and tissues, and evaluated their significance for the differentiation of malignant and benign tumors.